INSTALASI PEMBUMIAN DAN INSTALASI LISTRIK MUSHOLA AL MUTTAQIIN TEMBESI KIBING-BATU AJI BATAM - Hadiyanto, Gunawan Toto; Mardiono, Djoko Anwar; Jumadril, Jumadril JN; Kumala Sari, Intan (LPPM-Universitas Batam, 2024)
The condition of the electrical installation system in people's homes and especially places of pray (Mushola) in Tembesi Kalurahan Kibing, Batu Aji District, Batam City, most people still do not understand about electrical installations and there are still many things that do not comply with general regulations regarding electrical installations, apart from There are still many electrical installation connections carried out by the community themselves which do not comply with the provisions. Community service by providing counseling and going directly to see the location that is the target for carrying out service activities, namely the Al Muttaqiin prayer room. By holding community service (PKM), residents of Kibing Village will understand how to install electricity properly, correctly and safely. The equipment selected for installation in an electrical installation must meet applicable standards and must be suitable for its environment. Installation of equipment must comply with the provisions in PUIL, and match the equipment manufacturer's instructions. Electrical installations must be regularly inspected and tested for misuse, damage or poor installation, including loose connections. To protect against leakage currents, grounding and ELCB can be installed.In order to achieve an increase in public knowledge and understanding about the importance of electrical hazards, this activity needs to be sustainable